2023
DOI: 10.2105/ajph.2023.307228
|View full text |Cite
|
Sign up to set email alerts
|

Loopholes for Underage Access in E-Cigarette Delivery Sales Laws, United States, 2022

Abstract: Objectives. To comprehensively catalog and review state e-cigarette delivery sales laws as well as capture their scope and dimensions. Methods. We conducted an in-depth review to determine whether states had at least 1 form of e-cigarette delivery sales law. We coded laws for 5 key policy domains: (1) delivery terminology used in laws, (2) age verification requirements, (3) packaging label requirements, (4) permit or registration requirements, and (5) fines and penalties for violations. Results. Overall, 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 1 This growth in ENDS products coincided with the lack of consistent regulations and quality control, raising concerns about the safety and long-term health effects of ENDS, especially loopholes for youth access in ENDS delivery sales laws in the US. 2 , 3 Our study of US adults 4 showed high variability in using ENDS and cigarettes over time. We also found that an increase in ENDS use from 2015 to 2019 among adults led to a decrease [in an absolute term] in cigarette use.…”
mentioning
confidence: 83%
“… 1 This growth in ENDS products coincided with the lack of consistent regulations and quality control, raising concerns about the safety and long-term health effects of ENDS, especially loopholes for youth access in ENDS delivery sales laws in the US. 2 , 3 Our study of US adults 4 showed high variability in using ENDS and cigarettes over time. We also found that an increase in ENDS use from 2015 to 2019 among adults led to a decrease [in an absolute term] in cigarette use.…”
mentioning
confidence: 83%
“… 3 This is because ENDS have a high own-price elasticity, with the elasticity of demand being particularly large for the flavored version of the product. 3 But if current efforts to identify the loopholes in government regulation and policies introduced to restrict adolescents’ access to ENDS 4 achieve their intended objective, the high changeability in ENDS and cigarette use among US adults 1 may reverse the decline in cigarette use. Evidence for the positive cross-price elasticities of demand between e-cigarettes and cigarettes, with a possible economic substitution effect between them 3 strengthens this plausibility.…”
mentioning
confidence: 99%